2016
DOI: 10.1002/jbmr.2892
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Senescent Cells in the Bone Microenvironment

Abstract: Cellular senescence is a fundamental mechanism by which cells remain metabolically active yet cease dividing and undergo distinct phenotypic alterations, including upregulation of p16Ink4a, profound secretome changes, telomere shortening, and decondensation of pericentromeric satellite DNA. Because senescent cells accumulate in multiple tissues with aging, these cells and the dysfunctional factors they secrete, termed the senescence-associated secretory phenotype (SASP), are increasingly recognized as promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
474
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 416 publications
(517 citation statements)
references
References 51 publications
38
474
2
3
Order By: Relevance
“…Importantly, we found that increased osteocyte age was associated with an increase in markers of DNA damage, cellular senescence, and SASP in osteocyte-enriched cortical bone preparations from both male and female B6 mice, consistent with recent findings by others (57). The SASP may well influence the secretory profile of neighboring aged but healthy osteocytes, as well as the relatively young osteocytes formed during endosteal and intracortical remodeling (58).…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, we found that increased osteocyte age was associated with an increase in markers of DNA damage, cellular senescence, and SASP in osteocyte-enriched cortical bone preparations from both male and female B6 mice, consistent with recent findings by others (57). The SASP may well influence the secretory profile of neighboring aged but healthy osteocytes, as well as the relatively young osteocytes formed during endosteal and intracortical remodeling (58).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we used Palbociclib treatment (mimicking high p16 INK4a expression) to demonstrate that chondrocytes are responsive to CDK4/6 inhibition when cultured ex vivo under conditions that support proliferation. In line with reports of senescent features in other postmitotic cells such as neurons (Jurk et al., 2012) and osteocytes (Farr et al., 2016), our results demonstrate that the INK4a/ARF locus is potently activated with aging even in a cell type that is not affected by replicative exhaustion in vivo.…”
Section: Discussionmentioning
confidence: 50%
“…Of particular relevance is the recent finding that osteocytes exhibit features of cellular senescence with age, including expression of p16 INK4a and SASP markers (Farr et al., 2016). Our in vivo approach focused on the role of p16 INK4a in chondrocytes through the use of the Acan tm1(cre/ERT2)Crm allele that targets articular chondrocytes and meniscal cells (Henry et al., 2009), as well as a fraction of osteoblasts through direct conversion of hypertrophic growth plate chondrocytes (Ono, Ono, Nagasawa & Kronenberg, 2014; Zhou et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…6 A ). Rorβ expression was also significantly increased (fourfold) in osteocyte-enriched bone samples (14) from 12-month-old versus 6-month-old mice (Supporting Fig. 6 B ).…”
Section: Resultsmentioning
confidence: 91%